Pengaruh Metode Pembelajaran Peta Pikiran (Mind Mapping) terhadap Peningkatan Hasil Belajar Fisika Siswa Kelas VIII SMP Negeri 6 Pematangsiantar Tahun 2022 - Ismadi Sihombing; Sarma Dewi Kemala (Departement of Mathematics Education, 2023)
Indonesia's low education can be seen from the low student learning outcomes in various subjects. One of the subjects that students always have the lowest grades on and is most afraid of is physics. Various efforts have been made by the teacher in overcoming the problems mentioned above, such as conducting discussions and questions and answers in class and helping students who have difficulties in learning physics. One of the learning methods that can be used by the teacher is to apply the mind map method. Mind maps are a creative note-taking method that make it easier to remember large amounts of information. This study aims to determine the effect of the mind map learning method on the physics learning outcomes of class VIII students of SMP Negeri 6 Pematangsiantar year 2022. This type of research is a quasi-experimental. The population in the study were all 260 grade VIII students. Sampling was carried out by means of cluster random sampling, namely the experimental class VIII1 consisted of 35 people and the control class VIII2 consisted of 35 people. The instrument used is a learning test. Data processing uses an independent sample t-test. From the research results, the average post-test score for the experimental class was 75.43 with a standard deviation of 10.31 and the average post-test score for the control class was 64.43 with a standard deviation of 10.20. The results of the t test obtained a significance value in the experimental class = 0.894 > 0.05, then H0 was accepted, meaning that there was an influence of the Mind Mapping learning method on physics learning outcomes for class VIII students of SMP Negeri 6 Pematagsiantar.